PEMBERDAYAAN MASYARAKAT MELALUI RUMAH BELAJAR KOMUNITAS (RBK) BAGI MASYARAKAT BUTA AKSARA DI DESA YABEMA DISTRIK ELELIM KABUPATEN YALIMO - Lisye Iriana Zebua; Wigati Yektiningtyas; Rosye Hefmi R. Tanjung (JURNAL PENGABDIAN PAPUA, 2020)
Illiteracy is the basis of human knowledge. By reading humans can improve their quality. The purpose of this community service activity is to establish a Community Learning House (RBK) to the illiterate community in Yabema village, Elelim District, Yalimo Regency, so that the community is able to read, write and count. The activity method consists of six stages, namely problem identification, planning process, projection, assessment, evaluation, and monitoring. The results achieved from the community empowerment program through Community Learning Centers (RBK) for the illiterate community in Yabema Village have a significant influence in motivating participants, increasing readiness for learning, increasing the ability of calistung (reading, writing and arithmetic) and communication and enhancing functional skills (for example, can read identity card, write names, and make simple sentences). Keywords: Illiteracy, Community Learning Centers, Yabema, Yalimo